A LANE TRACKING ALGORITHM FOR LOW-COMPUTATIONAL-POWER MICROCONTROLLER-CONTROLLED AUTONOMOUS VEHICLE MODELS - KOZŁOWSKI, Maciej; CZEREPICKI, Andrzej; DZIDO, Piotr (Problemy Transportu, 2024)
At work, three tasks were presented: road lane detection and trajectory estimation, environment mapping, and the application of a neural network. All these tasks are based on the results of the lane detection method. The presented lane detection method stands out due to the execution of an interpolation transformation for all previously detected edge points. This transformation transfers these points to a “bird’s-eye” coordinate system and distributes them on a grid. Road lanes are identified by a lane feature filter based on the analysis of the distances between unique points. This allows lane views to be obtained in a coordinate system while preserving the distance condition. The road environment map is constructed from the obtained images using a probabilistic algorithm called Distributed Particle-SLAM (DP-SLAM). Based on the map result, a method for representing characteristic points describing the path of road lanes in each incoming camera image has been developed. These points are then used for training the neural network. The neural network solves a regression task for the coordinates of the points on the road lanes, enabling the identification of coefficients for parabolic fitting. Validation has been performed.